(untitled) - Bianchi, Giovanni (New York, 2007)
Filtering unwanted information out of any electronic component is easier
Keywords: Electric filters,Electric filters,Hệ thống lọc điện,Hệ thống lọc điện; Mathematical models,Design and construction,Mô hình toán học,Thiết kế và xây dựng